EFFECTIVE METHODS AND MEANS OF TEACHING A FOREIGN LANGUAGE - Amanov, Alisher (Журнал иностранных языков и лингвистики, 2023)
Our article will cover the methodology of teaching a foreign language, the history of its development as a science, the types of modern methods used in the methodology of teaching a foreign language and their use.